Structure of the Toll-Spatzle complex, a molecular hub in Drosophila development and innate immunity. - Parthier, C.; Stelter, M.; Ursel, C.; Fandrich, U.; Lilie, H.; Breithaupt, C.; Stubbs, M.T. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Drosophila Toll receptors are involved in embryonic development and the immune response of adult flies. In both processes, the only known Toll receptor ligand is the human nerve growth factor-like cystine knot protein Spätzle. Here we present the crystal structure of a 1:1 (nonsignaling) complex of the full-length Toll receptor ectodomain (ECD) with the Spätzle cystine knot domain dimer. The ECD is divided into two leucine-rich repeat (LRR) domains, each of which is capped by cysteine-rich domains. Spätzle binds to the concave surface of the membrane-distal LRR domain, in contrast to the flanking ligand interactions observed for mammalian Toll-like receptors, with asymmetric contributions from each Spätzle protomer. The structure allows rationalization of existing genetic and biochemical data and provides a framework for targeting the immune systems of insects of economic importance, as well as a variety of invertebrate disease vectors.